Analisis Program Subuh Berkah untuk Membentuk Karakter Religius Mahasiswa Universitas Merdeka Malang: An Analysis of the Subuh Berkah Program in Developing the Religious Character of Students at Universitas Merdeka Malang - Moh. Nur Alimin; Dwi Dian Wigati; Siti Nailatur Roihana; Sella Kharisma Nur Ardhila (Educan, 2025)
The phenomenon of moral degradation is increasingly prevalent among university students. This is evident in the rise of promiscuity, alcohol parties, illicit sexual behavior, and a general lack of tolerance both within and across religious boundaries. Universitas Merdeka Malang stands out as one of the few, if not the only, higher education institutions that is actively and systematically striving to foster students’ religious character through the Subuh Berkah (Blessed Dawn) Program. This study aims to analyze the effectiveness of the Subuh Berkah Program in developing the religious character of students at Universitas Merdeka Malang. The research employed a qualitative approach. Data were collected through participant observation, interviews, and documentation. The data analysis technique used was descriptive analysis, consisting of data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through triangulation. The findings of the study reveal: (1) The Subuh Berkah Program has succeeded in shaping students’ religious character, particularly in the aspects of piety, sincerity, tolerance, non-violence, and discipline. Although the outcomes have not yet fully aligned with the religious character indicators outlined by the Ministry of National Education, the program is considered effective in fostering tolerant attitudes among students. (2) The implementation of the Subuh Berkah Program involves habitual practices such as congregational dawn prayers, collective remembrance (dzikir), religious study sessions (kajian subuh), group isyraq prayers, istighosah (supplicatory prayers), and communal breakfast. The program has received positive responses and strong support, especially from students’ parents. It has contributed to a more comprehensive understanding of Islam among students and has helped optimize the teaching and learning of Islamic Religious Education.